Characterization of a Multidrug-ResistantCitrobacter pasteurii isolate carrying blaKPC-2 from municipal wastewater. Issue 5 (27th May 2022) - Ryan, Michael P; Slattery, Shannon; Pembroke, J Tony
Abstract : A carbapenem-resistant strain, UL-CPE-01, was isolated from a domestic wastewater treatment plant and subjected to antibiotic susceptibility testing showing resistance to a wide range of antibiotics. Complete genome and bioinformatic analysis of UL-CPE-01 was performed to investigate the nature of its resistance determinants and the strain identified as Citrobacter pasteuriibased onANI score. Citrobacter spp. are part of the normal human and animal intestinal flora and the UL-CPE-01 Citrobacter pasteuriistrain detected here is closely related to Citrobacter freundii, which is an emerging opportunistic nosocomial pathogen. UL-CPE-01 showed both phenotypic and genotypic multiple resistance to aminoglycoside, β-lactams, sulfonamides, fluoroquinolone, rifampicin, phenicol and macrolide antibiotics. The UL-CPE-01 genome revealed 16 acquired antimicrobial resistance gene (ARGs) conferring resistance to eight different antibiotic groups: dfrA12 (trimethoprim); sul1 (sulfonamide); mph(A), mph(E) and msr(E) (macrolide); qnrB4 and aac(6′)-Ib-cr (fluoroquinolone); blaDHA-1, blaOXA-1, blaCMY-77, blaOXA-10, blaTEM-1B, blaKPC-2(β-lactams); arr-3 (rifampicin); catB3 and catA1 (chloramphenicol) and aac(6′)-Ib-cr, aadA2 and ant(2″)-Ia (aminoglycoside). The novel blaKPC-2 determinant was found to be associated with in a Tn4401-like element.